2019
DOI: 10.5327/z167944352019392
|View full text |Cite
|
Sign up to set email alerts
|

Profile of disability retirement among civil servants at Oswaldo Cruz Foundation, 2012–2016

Abstract: | Background: Disability retirement, an outcome of permanent incapacity for work, represents 14.5% of pensions granted by the Brazilian National Social Security Institute. However, there are no data available for civil servants. Objective: To describe the epidemiological profile of disability retirement among employees of Oswaldo Cruz Foundation (FIOCRUZ) in the period from 2012 to 2016. Methods: Cross-sectional study in which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 56 publications
1
5
0
4
Order By: Relevance
“…It is believed that the public service structure and organization are obstacles for workers to control the work performed, contributing to early retirements. These data are similar to those from another study conducted with retirees due to disabilities, which identified that they were still individuals of productive age (21) . This fact exerts impacts on the Brazilian social security system, which has a history of deficits, as well as on financial deficits for workers, who often did not reach the necessary contribution time to realize full retirement (22) .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is believed that the public service structure and organization are obstacles for workers to control the work performed, contributing to early retirements. These data are similar to those from another study conducted with retirees due to disabilities, which identified that they were still individuals of productive age (21) . This fact exerts impacts on the Brazilian social security system, which has a history of deficits, as well as on financial deficits for workers, who often did not reach the necessary contribution time to realize full retirement (22) .…”
Section: Discussionsupporting
confidence: 86%
“…Age below the established for retirement among those distanced due to disabilities was identified in different realities, with various groups of workers around the world 21 , 23 . This fact only ratifies the importance of this theme and of implementing measures to prevent early exit from the labor market.…”
Section: Discussionmentioning
confidence: 99%
“…Se cree que la estructura y organización del servicio público son obstáculos para que el trabajador tenga control sobre el trabajo que realiza, lo que contribuye a que haya bajas anticipadas. Esos datos son similares a los de otro estudio con jubilados por invalidez, que identificó que eran personas que aún tenían edad para trabajar (21) .…”
Section: Discussionunclassified
“…Se identificó que jubilados por invalidez con diferentes realidades y pertenecientes a diferentes grupos de trabajadores en todo el mundo no habían alcanzado la edad mínima para jubilarse (21,23) . Este hecho confirma lo importante que es este tema y que se tomen medidas para evitar la salida anticipada del mercado laboral.…”
Section: Discussionunclassified
“…Acredita-se que a estrutura e a organização do serviço público são obstáculos para que o trabalhador tenha o controle sobre o trabalho desempenhado, contribuindo para os afastamentos precoces. Esses dados são análogos aos de outro estudo com aposentados por invalidez, o qual identificou que eles ainda eram pessoas em idades produtivas (21) . Esse fato provoca impactos no sistema previdenciário brasileiro que apresenta um histórico deficitário, como também, em déficits financeiros ao trabalhador, que, muitas vezes, não alcançou o tempo de contribuição necessário para perceber a aposentadoria integral (22) .…”
Section: Discussionunclassified